2013
DOI: 10.1158/1078-0432.ccr-13-1186
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NAPRT1 Expression by Tumor-Specific Promoter Methylation Provides a Novel Predictive Biomarker for NAMPT Inhibitors

Abstract: Purpose: We sought to identify predictive biomarkers for a novel nicotinamide phosphoribosyltransferase (NAMPT) inhibitor.Experimental Design: We use a NAMPT inhibitor, GNE-617, to evaluate nicotinic acid rescue status in a panel of more than 400 cancer cell lines. Using correlative analysis and RNA interference (RNAi), we identify a specific biomarker for nicotinic acid rescue status. We next determine the mechanism of regulation of expression of the biomarker. Finally, we develop immunohistochemical (IHC) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 33 publications
5
61
0
Order By: Relevance
“…In cancer cells, low Naprt1 expression may be mediated by NAPRT1 promoter methylation (Shames et al, 2013). In keeping with these prior findings, we found that the NAPRT1 promoter CpG island was hypermethylated in our cell lines with very low Naprt1 expression, including all IDH1 mutant lines (Figure 4K).…”
Section: Resultsmentioning
confidence: 99%
“…In cancer cells, low Naprt1 expression may be mediated by NAPRT1 promoter methylation (Shames et al, 2013). In keeping with these prior findings, we found that the NAPRT1 promoter CpG island was hypermethylated in our cell lines with very low Naprt1 expression, including all IDH1 mutant lines (Figure 4K).…”
Section: Resultsmentioning
confidence: 99%
“…Because Myc has been reported to induce NAMPT expression (35) and Naprt1 expression is known to modulate sensitivity to NAMPT inhibitors (36, 37), we evaluated the expression of Naprt1 as well as NAMPT in our GBM tumorsphere lines. We found that NAMPT expression was similar in all GBM tumorsphere lines tested (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest that select tumor types are "addicted" to the NAMPT-dependent salvage pathway due to the downregulation of alternative NAD 1 production pathways and are therefore more sensitive to NAMPT inhibition. 17,18 Several NAD 1 consumer proteins, such as CD38, poly (ADP-ribose) polymerase, and sirtuins, have been shown to manage DNA repair mechanisms and mediate cancer disease progression by protecting cells during nutrient-deficient events. [19][20][21][22][23][24] In the absence of NAD 1 , both classes of proteins lose their cytotoxic protective features, making NAD 1 reduction a potential target for cancer therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%